ONLINE GAMBLING AND FAMILY RESILIENCE: ISLAMIC FAMILY LAW IN BOJONEGORO REGENCY, INDONESIA - Khurul Anam; Lisa Aminatul Mukaromah; Vesti Dwi Cahyaningrum; Windawati Laily Nuraini (Universitas Syiah Kuala, 2026)
The rapid growth of online gambling has emerged as a structural threat to family resilience in Indonesia. This article investigates online gambling as a primary catalyst for marital breakdown through the lens of Islamic Family Law, specifically questioning its impact on family stability and the fulfilment of child protection rights. The study utilizes a normative-empirical juridical method, integrating the analysis of Islamic legal norms, such as the Qur'an, Hadith, and the Compilation of Islamic Law (KHI), with empirical data and evidentiary practices from the Bojonegoro Religious Court. Findings indicate that online gambling is prohibited as maisir and constitutes a fundamental violation of the husband’s obligations as qawwam (leader and protector), particularly regarding financial maintenance (nafkah). Furthermore, the study reveals that courts are adopting a progressive legal interpretation of Article 116 letter (f) KHI by accepting digital evidence, such as betting histories and transaction screenshots, to prove the persistent conflict necessary for divorce. The article contributes to legal knowledge by offering a replicable normative-empirical framework for jurisdictions facing digital-era family law challenges. It shifts academic focus from general gambling to the specific, addictive nature of online platforms and provides a basis for legal reform, including mandating psychological counselling for digital addiction within court mediation processes. This study underscores that protecting family resilience requires an integrated approach of legal, social, and religious enforcement.